A Systematic Literature Search on Psychological First Aid: Lack of Evidence to Develop Guidelines - Dieltjens, Tessa; Moonens, Inge; Van Praet, Koen; De Buck, Emmy; Vandekerckhove, Philippe (PLOS ONE, 2014)
Background Providing psychological first aid (PFA) is generally considered to be an important element in preliminary care of disaster victims. Using the best available scientific basis for courses and educational materials, the Belgian Red Cross-Flanders wants to ensure that its volunteers are trained in the best way possible. Objective To identify effective PFA practices, by systematically reviewing the evidence in existing guidelines, systematic reviews and individual studies. Methods Systematic literature searches in five bibliographic databases (MEDLINE, PsycINFO, The Cochrane Library, PILOTS and G-I-N) were conducted from inception to July 2013. Results Five practice guidelines were included which were found to vary in the development process (AGREE II score 20–53%) and evidence base used. None of them provides solid evidence concerning the effectiveness of PFA practices. Additionally, two systematic reviews of PFA were found, both noting a lack of studies on PFA. A complementary search for individual studies, using a more sensitive search strategy, identified 11 237 references of which 102 were included for further full-text examination, none of which ultimately provides solid evidence concerning the effectiveness of PFA practices. Conclusion The scientific literature on psychological first aid available to date, does not provide any evidence about the effectiveness of PFA interventions. Currently it is impossible to make evidence-based guidelines about which practices in psychosocial support are most effective to help disaster and trauma victims.